Fields of protest : women's movements in India - Ray, Raka (Social movements, protest, and contention, 1999)
The women's movement in India has a long and rich history in which millions of women live, work, and struggle to survive in order to remake their family, home, and social lives. Using an innovative and comparative perspective, Ray offers a unique look at Indian activist women and adds a new dimension to the study of women's movements on a global level.